Endoscopic retrieval of dental implants from the maxillary sinus - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2006)
Endoscopic sinus surgery has been performed for various indications in maxillofacial surgical practices. It has been utilized for assessment of antral pathologies, removal of foreign bodies, orthognathic procedures, and treatment of facial fractures. In the cases presented, 3 dental implants which were displaced into maxillary sinuses were removed by endoscopic sinus surgery. Transantral endoscopic surgery is a reliable, minimally invasive method for retrieving displaced objects from the maxillary antrum with minimal complications.
Keywords: dental implant; endoscopic surgery; implant displacement; maxillary sinus; FOREIGN-BODY; FRACTURES; REMOVAL